Predicting Shelter Residence in Women Experiencing Recent Intimate Partner Violence. (April 2013) - Galano, Maria M.; Hunter, Erin C.; Howell, Kathryn H.; Miller, Laura E.; Graham-Bermann, Sandra A.
This study sought to determine factors associated with shelter residence in women with recent histories of intimate partner violence (IPV). The sample included 113 women, approximately half of whom resided in a shelter over the past year. Participating women provided demographic information and completed standardized measures of IPV, trauma, and depression. Ethnicity, income, housing stability, and mental health, but not violence exposure, differentiated the shelter and community groups. Trauma symptoms, housing instability, and ethnicity best predicted shelter residence. Future research should focus on determining what types of services and interventions will best address the unique needs of each population.